2001
DOI: 10.1002/1096-8628(20010201)98:4<357::aid-ajmg1108>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

C677T variant form at the MTHFR gene and CL/P: A risk factor for mothers?

Abstract: Maternal folic acid supplementation in early pregnancy has been suggested to play a role in the prevention of nonsyndromic orofacial cleft, i.e., cleft lip with or without cleft palate (CL/P). Moreover, some authors demonstrated association of the C-->T mutation (C677T), converting an alanine to a valine residue in 5,10-methylenetetrahydrofolate reductase (MTHFR) gene, with other congenital anomalies such as neural tube defects (NTDs). Because of MTHFR's involvement in the metabolism of folate, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 15 publications
5
77
1
8
Order By: Relevance
“…Indeed, it codes for an enzyme of the folate pathway involved in different congenital malformations (Czeizel & Dudas 1992 ;Shaw et al 1995). In a recent association study, carried out with the same family sample as the present work, an increased frequency of the C677T MTHFR mutation in mothers of OFC patients was detected (Martinelli et al 2001). Although this result needs to be confirmed, we proposed that the mother's genotype at the MTHFR gene may increase the risk of having affected children.…”
Section: supporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, it codes for an enzyme of the folate pathway involved in different congenital malformations (Czeizel & Dudas 1992 ;Shaw et al 1995). In a recent association study, carried out with the same family sample as the present work, an increased frequency of the C677T MTHFR mutation in mothers of OFC patients was detected (Martinelli et al 2001). Although this result needs to be confirmed, we proposed that the mother's genotype at the MTHFR gene may increase the risk of having affected children.…”
Section: supporting
confidence: 60%
“…In the second stage of this study (with a resolution of 5 cM) they found a non-parametric linkage score (NPL) of 2n35 at the region 1p36, between the D1S214 and D1S2697 markers. Recently, some authors Martinelli et al 2001) investigated the involvement of the folate pathway in OFC aetiology. In particular, they identified the C677T mutation in the methylenetetrahydrofolate reductase gene (MTHFR), which maps in 1p36, as a susceptibility factor in nonsyndromic OFC.…”
mentioning
confidence: 99%
“…Folic acid derivatives provide essential single carbon units fro nucleic acid synthesis and methylation reactions both of which are essential for cell division, gene expression and maintenance of chromosome structure during fetal development. It is interesting to note that the case control studies have indicated an effect of the maternal MTHFR genotype rather than that of the affected child (Martinelli et al, 2001;Prescott et al, 2002;Pezzetti et al, 2004). The association of MTHFR polymorphisms with the increased risk of OFC supports the protective effect of maternal use of multivitamins containing folic acid with respect to the occurrence of orofacial clefts (Bailey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, in an, homozygosity for the C677T allele was associated with an increased risk for isolated cleft palate (OR =3.2; 95 percent CI: 1.3, 7.9) and possibly for cleft lip with or without cleft palate (OR =1.6; 95 percent CI: 0.8, 3.4) [92]. An increased risk due to the maternal MTHFR genotype (677 T or 1282A alleles) on predisposition to CL/P was suggested by several studies [14,93,94,95,96]. In a recent study from china reports moderate association between the 677C-T polymorphism and non_syndromic cleft lip/palate in families from northern China but not in those from southern China suggesting the genetic heterogeneity [97].…”
Section: Association Studiesmentioning
confidence: 98%